THE ROLE OF TRUST WITHIN THE ORGANIZATION IN ACHIEVING ORGANIZATIONAL SUCCESS: AN EXPLORATORY STUDY IN THE GENERAL DIRECTORATE OF EDUCATION - AL-RUSAFA FIRST - Nuha Abdullah Anber (Modern American Journals, 2025)
The current research aims to identify the level of organizational culture within the Al-Rusafa First Education Directorate, as well as to demonstrate the level of influence of the main variable (organizational culture) with its dimensions, which are (trust in superiors, trust in colleagues, and trust in the organization) on the dependent variable (organizational success) with its dimensions, which are (resources, organizational structure, management, processes, and knowledge management). The research was applied in the Iraqi Ministry of Education, specifically the Al-Rusafa First Education Directorate, and a sample of employees in the directorate was randomly selected, amounting to (60) employees. The data were analyzed through the statistical analysis program (SPSS V.26), and the arithmetic means and standard deviation were adopted as tools in the practical aspect. The research concluded with a number of results, the most important of which is that trust in the institution is the most influential factor in almost every aspect of organizational success, especially in resources and organizational structure.
Keywords: Trust within the organization, organizational success, Iraqi Ministry of Education